Othello [videorecording (DVD)] - Welles, Orson, 1915-1985; Welles, Orson, 1915-1985; Mac Liammóir, Micheál, 1899-1978; Cloutier, Suzanne, 1923-2003-; Coote, Robert, 1909-1982; Shakespeare, William, 1564-1616 (Criterion collection, 2017)
Dramatization of William Shakespeare's play in which the evil Iago plants the seeds of doubt in Othello's mind about Desdemona's fidelity.